Effects of moisture content and inner drum rotation speed on the shelling performance of a melon sheller (2012)
Melon shelling is an intermediate stage in melon processing and needs to be given much attention for most of the farmers still employ manual means of shelling which is time consuming, energy demanding and resulting in low income. A melon shelling machine using a rubbing action motion in peeling was designed and fabricated. The machine which is powered by 1Hp, 1400rpm electric motor consists of a hopper, the shelling chamber (rotating inner serrated drum and a fixed cylindrical ring), an outlet unit, and a motor seat. An inner drum rotation speed of 350rpm was achieved through the use of a big driven pulley to obtain an appreciable shelling performance of 58.68% with percentage loss of 16.5% at percentage moisture content of 23.08%.